Business sustainability framework : theory and practice - Rezaee, Zabihollah, 1953- (Routledge, 2025)
"Providing a practical and accessible introduction to a complex yet essential area, Business Sustainability Framework enables readers to integrate and report on sustainability reporting from business and accounting perspectives. The author explores how organizations of all sizes can adopt an integrated strategic approach to business sustainability, encompassing planning, performance, reporting, and assurance. Grounded in the latest research, the book is updated to include topics such as shareholder and stakeholder governance models, business sustainability factors and initiatives, sustainability theories, standards and best practices, the use of AI, and financial reporting and auditing initiatives. An ideal introduction for advanced undergraduate and graduate students of sustainability governance, performance, risk, reporting, and assurance, this textbook equips readers with the knowledge and skills necessary to become successful business leaders in sustainability"--